Measurement of the across-plane conductivity of YSZ thin films on silicon - Navickas, E. (Solid State Ion, 2012)
Across-plane conductivity measurements on ion conducting thin films of a few ten nanometers thickness are challenging due to frequently occurring short-circuits through pinholes in the layer. In this contribution, a method is proposed which allowed across-plane conductivity measurements on yttria stabilized zirconia (YSZ) layers with thicknesses as low as 20 nm. YSZ layers were prepared onto silicon substrates with a thin native silica interlayer and the across-plane conductivity was measured on circular microelectrodes by impedance spectroscopy. The silica interlayer exhibits strongly blocking behavior, which helps to avoid short-circuits through pinholes. Different relaxation frequencies of YSZ and silica make separation of these layers possible. An equivalent circuit is suggested, which allows extraction of YSZ properties, and its validity is proven by varying microelectrodes size and layer thickness. All parameters yield the expected behavior.